JON M. CHU’S FILM CRAZY RICH ASIANS: THE INTERPLAY OF WESTERN AND EASTERN CULTURES - I Gusti Ngurahe Ade Wiraldy; Daniel Ginting (English Department of Faculty of Tarbiyah and Teacher Training, 2021)
The film Crazy Rich Asians released in 2018 represents a complexity of social interactions among people with different cultural background. The adaptability to new environments is not always easy; yet, the main character is persistent and capable of maintaining her identity. Being an American born Chinese, Rachel Wu, the main character is depicted as a